Evaluation of Stability and Geotechnical Performance of Hopper Retaining Walls Using PLAXIS 2D (Hardening Soil Model) - Shohib, Muhammad; Teki Tjendani, Hanie; Purnama, Jaka (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2025)
This study aims to evaluate the geotechnical–structural performance of the retaining walls that form a dump pocket around the ROM hopper of a crushing facility. The modeling was divided into three sections—Section 1 (1 CSP Ø600 + 2 SQP 250×250), Section 2 (1 CSP Ø600 + 3 SQP 250×250), and Section 3 (2 CSP Ø600)—and was performed using two-dimensional finite element analysis (PLAXIS 2D) with the Hardening Soil model. Staged construction was simulated from K₀ conditions to a fill height of 1–5.9 m, followed by an additional surface load of 20 kPa. Service performance was verified against project criteria, while global stability was obtained using strength reduction. The results show that the safety factor decreases with increasing fill height, but all alternatives remain acceptable under the most critical conditions (FS ≈ 1.52–1.59). Peak deformation in the final stage was Ux ≈ 0.064–0.068 m and Uy ≈ 0.009–0.017 m, which was within the SLS (Serviceability Limit State) limits. Peak forces include wall bending moments ≈66–92 kNm/m concentrated at the wall–pile cap joints. Multi-criteria assessment (stability, serviceability, and material indicators) placed Section-2 as the preferred alternative because it combines adequate stability, lowest serviceability deformation, and competitive material usage. These findings support the emphasis on detailing the wall–pile cap joint zone and confirm the feasibility of implementing the recommended configuration.